Reaction-sintered LAGP solid electrolytes with MoS2 coating for improved stability with Li metal. Issue 23 (1st December 2022) - Baek, Seung Jin; Cha, Eunho; Kim, Dong Gyu; Yun, Jong Hyuk; Kim, Do Kyung
Abstract: Regarded as one of the most promising solid electrolytes, Li1.5 Al0.5 Ge1.5 (PO4 )3 (LAGP) is characterized by high ionic conductivity at room temperature with good chemical stability. However, its application in all-solid-state batteries is hindered by the high-temperature synthesis and poor interface contact with lithium metal. Herein, we propose the reaction-sintering strategy by controlling the heat treatment to prepare dense and highly conductive LAGP at lower temperatures. The samples calcined at 500 °C followed by 800 °C sintering exhibit a relative density as high as 94.2% and a conductivity of 2.3 × 10 −4 S cm −1 at room temperature, which indicates the reaction-induced sintering is responsible for the enhanced densification of LAGP. In addition, MoS2 coating is facilely applied on the LAGP surface to simultaneously reduce the interfacial resistance and prevent electrolyte degradation. As a result, the MoS2 @LAGP symmetric cells maintain stable cycling performance for more than 70 h at the current density of 0.5 mA cm −2, which suggests that the interfacial stability is established between solid electrolytes and lithium electrodes.